Determination of the collision rate coefficient between charged iodic acid clusters and iodic acid using the appearance time method. Issue 2 (1st February 2021) - He, Xu-Cheng; Iyer, Siddharth; Sipilä, Mikko; Ylisirniö, Arttu; Peltola, Maija; Kontkanen, Jenni; Baalbaki, Rima; Simon, Mario; Kürten, Andreas; Tham, Yee Jun; Pesonen, Janne; Ahonen, Lauri R.; et al.
Abstract: Ions enhance the formation rate of atmospheric aerosol particles, which play an important role in Earth's radiative balance. Ion-induced nucleation involves the stepwise accretion of neutral monomers onto a molecular cluster containing an ion, which helps to stabilize the cluster against evaporation. Although theoretical frameworks exist to calculate the collision rate coefficients between neutral molecules and ions, they need to be experimentally confirmed, ideally under atmospherically relevant conditions of around 1000 ion pairs cm −3 . Here, in experiments performed under atmospheric conditions in the CERN CLOUD chamber, we have measured the collision rate coefficients between neutral iodic acid (HIO3 ) monomers and charged iodic acid molecular clusters containing up to 11 iodine atoms. Three methods were analytically derived to calculate ion-polar molecule collision rate coefficients. After evaluation with a kinetic model, the 50% appearance time method is found to be the most robust. The measured collision rate coefficient, averaged over all iodine clusters, is (2.4 ± 0.8)×10 −9  cm 3 s −1, which is close to the expectation from the surface charge capture theory.